The road to purpose-fit selection of the construction manager - Burger, Michelle (University of Pretoria, 2018)
A shortage in experienced skilled construction managers is foreseen in the near future. A big contributing factor is the entering of non-purpose-fit candidates into construction management programmes. Valuable time and resources are wasted on students enrolled in construction management programmes, entering construction management positions and ultimately leaving these positions due to a common misconception of the actual work conditions of a construction manager. The philosophical framework constituted an underlying pragmatic philosophical underpinning. The researcher opted for mixed methods and action research approached within this study. The research study was restricted to cross-sectional time-horizons as the thesis had to be completed within a specific time frame. The aim of this research study is to suggest a purpose-fit selection of the construction manager in South Africa. This will link with the soft skills in the competency domain that is currently needed in the industry and in the profession itself. It is suggested that construction management students should do practical work for a year before they start their studies. This will give them a better understanding of the work conditions, pressure and work-life balance associated with the construction industry, as this is not tested in the online SAPI personality test. Tertiary education in construction management and proper practical experience are crucial; but without the necessary soft skills and purpose-fit personality profile, the construction manager would not be successful on a project.